Empowerment of Harapan Farmer Group through Innovation of Processed Orange Peel Products in Baruah Gunuang, Payakumbuh - Suryani; Rahim, Farida; Andri, Gus; Arikhman, Nova; Lestari, Rinda (Majalah Ilmiah UPI YPTK, 2025)
This community service was carried out at the Harapan Farmers Group in Jorong Baruah Gunuang, Bukit Barisan District, which faces the problem of low income and lack of utilization of orange peel waste. This activity aims to increase people's income through: 1) innovation in processing orange peel into products of economic value, such as candied orange peel, orange jam, orange jelly, and natural pesticides. Next 2) knowledge of processing management and the results of innovation. The methods used include counseling, training, and direct assistance to members of farmer groups. The results of the activity showed an increase in knowledge from 42% to 91% and members had skills in processing orange peels, as well as orange juice, from the leftover oranges selected from sales to middlemen. So the formation of several innovative orange-based products, as well as the emergence of new business opportunities that have the potential to increase group income. Likewise, there is already a brand of the product and is in the process of obtaining a PIRT permit from the Health Office. This service activity proves that the use of orange peel waste not only reduces environmental problems, but is also able to provide economic added value for the community.often presented separate from the article, so it must be able to stand alone.